THE EFFECTS OF PERCEIVED AND ACTUAL FINANCIAL LITERACY ON FINANCIAL BEHAVIORS. (4th September 2015) - Allgood, Sam; Walstad, William B.
Abstract : A combined measure of financial literacy that includes both a test score of actual financial literacy and a self‐rating of overall financial literacy is used in this study. We find that the combined measure appears to provide greater understanding about how financial literacy affects financial behaviors. A large national survey of U.S. adults and households ( n = 28, 146) was used to investigate how this overall financial literacy is likely to change financial behaviors across five financial topics: credit cards, investments, loans, insurance, and financial advice. For each topic, we include 4–5 financial behaviors (22 in total) to demonstrate the consistency of the findings within and across topics. Although we are unable to identify a causal relationship, the results from the probit analysis show that both actual and perceived financial literacy appear to influence financial behaviors and that perceived financial literacy may be as important as actual financial literacy. ( JEL D14, G00)